1998
DOI: 10.1038/27215
|View full text |Cite
|
Sign up to set email alerts
|

Cripto is required for correct orientation of the anterior–posterior axis in the mouse embryo

Abstract: The anterior-posterior axis of the mouse embryo is established by two distinct organizing centres in the anterior visceral endoderm and the distal primitive streak. These organizers induce and pattern the head and trunk respectively, and have been proposed to be localized through coordinate cell movements that rotate a pre-existing proximal-distal axis. Here we show that correct localization of both head- and trunk-organizing centres requires Cripto, a putative signalling molecule that is a member of the EGF-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
452
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(477 citation statements)
references
References 30 publications
23
452
0
2
Order By: Relevance
“…In cripto mutant embryos, the distal epiblast acquired neural fate (Ding et al, 1998). This further indicated that the AVE, located distally in Cripto mutant embryos, has important roles in neural induction.…”
Section: Expression Of Endodermal Genes In the Distal Epiblast In Dvementioning
confidence: 81%
See 2 more Smart Citations
“…In cripto mutant embryos, the distal epiblast acquired neural fate (Ding et al, 1998). This further indicated that the AVE, located distally in Cripto mutant embryos, has important roles in neural induction.…”
Section: Expression Of Endodermal Genes In the Distal Epiblast In Dvementioning
confidence: 81%
“…The following digoxigenin-labeled riboprobes were used for this study: T (Wilkinson et al, 1990), Fgf8 (Crossley andMartin, 1995), Cripto (Ding et al, 1998), Nodal (Conlon et al, 1994), Cer1 (Shawlot and Behringer, 1995), Foxa2 (Sasaki and Hogan, 1994), Wnt3 (Liu et al, 1999), Flk1 (Yamaguchi et al, 1993), Otx2 (Ang and Constam, 2004), Oct4 (Rosner et al, 1990), and TTR (Makover et al, 1988).…”
Section: Whole Mount In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…First, polarity and, therefore, pattern appears to already exist in the epiblastal ectoderm before gastrulation as evinced by asymmetric patterns of gene expression typically encountered within epiblast (e.g., Bmp4,Otx2,Fgf8,T [Brachury],Cripto,Wnt3,Nodal,Hesx1,Hex,, VE-1, Lim1 [Lhx1], GATA, Dlx, and Dkk1; Lawson et al, 1991;Lawson and Pedersen, 1992;Dono et al, 1993;Simeone et al, 1993;Ang and Rossant, 1994;Crossley and Martin, 1995;Belo et al, 1997;Varlet et al, 1997;Eyal-Giladi, 1997;Beddington and Robertson, 1998;Biben et al, 1998;Ding et al, 1998;Shawlot et al, 1998;Thomas et al, 1998;Liu et al, 1999;Pera et al, 1999;Crossley et al, 2001;Tian et al, 2002;Chapman et al, 2002). This asymmetry is mirrored by the underlying hypoblast (visceral endoderm;e.g., Otx2, Lim1, Hesx1, Hex, HNF3␤, Lefty1, Nodal (Acampora et al, 1995;Thomas and Beddington, 1996;Belo et al, 1997;Filosa et al, 1997;Varlet et al, 1997;Thomas et al, 1998;Meno et al, 1999;Shimono and Berhinger, 1999;Kim...…”
Section: First Perambulations: Polarity and Pattern In The Pregastrulmentioning
confidence: 99%
“…The Nodal ligand binds a receptor complex that includes Activin type 1 and type 2 receptors (Whitman, 2001), together with an EGF-CFC-type coreceptor (Shen et al, 1997;Ding et al, 1998;Zhang et al, 1998;Dorey and Hill, 2006;Onuma et al, 2006). Lefty, a divergent member of the TGF␤ family whose transcription is directly regulated by Nodal signaling, is one of the principal extracellular feedback inhibitors of Nodal signaling (Meno et al, 1996(Meno et al, , 1999Thisse and Thisse, 1999;Cheng et al, 2000;Tanegashima et al, 2000;Branford and Yost, 2002;Cha et al, 2006).…”
Section: Introductionmentioning
confidence: 99%